The Influence of Banking Financial Performance on Company Value of Banks Listed on the Indonesia Stock Exchange in 2020-2024 - Ni Kadek Gea Aswina Wulandari; Burhanudin (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to examine the effect of financial performance consisting of non-performing loans, loan-to-deposit ratio, managerial ownership, return on assets, and capital adequacy ratio on company value. This study uses a quantitative method. The population used in this study is banking companies listed on the Indonesia Stock Exchange in the period 2020-2024. This data was accessed through the website www.idx.com and the company's official website. This study used a purposive sampling technique to obtain 85 observational data. Data were analyzed using panel data analysis techniques with the Eviews 12 tool. Based on the results of the study, it shows that non-performing loans, loan-to-deposit ratio, and capital adequacy ratio have a positive but insignificant effect on company value, managerial ownership has a negative but significant effect on company value, return on assets has a negative but insignificant effect on company value